Electron cryomicroscopy comparison of the architectures of the enveloped bacteriophages phi6 and phi8. - Jäälinoja, H; Huiskonen, J; Butcher, S (2007)
The enveloped dsRNA bacteriophages phi6 and phi8 are the two most distantly related members of the Cystoviridae family. Their structure and function are similar to that of the Reoviridae but their assembly can be conveniently studied in vitro. Electron cryomicroscopy and three-dimensional icosahedral reconstruction were used to determine the structures of the phi6 virion (14 A resolution), phi8 virion (18 A resolution), and phi8 core (8.5 A resolution). Spikes protrude 2 nm from the membrane bilayer in phi6 and 7 nm in phi8. In the phi6 nucleocapsid, 600 copies of P8 and 72 copies of P4 interact with the membrane, whereas in phi8 it is only P4 and 60 copies of a minor protein. The major polymerase complex protein P1 forms a dodecahedral shell from 60 asymmetric dimers in both viruses, but the alpha-helical fold has apparently diverged. These structural differences reflect the different host ranges and entry and assembly mechanisms of the two viruses.